Commercial Product Development of Fried Kluai Khai Crisps for Klauy Krob Thong Baansalasamhlang Community Enterprise, Nakhon Si Thammarat Province - Pimpa, Benchamaporn; Sutthirak, Pornpong (Area Based Development Research Journal, 2022)
Kluai Krob Thong Bansalasamlang Community Enterprise in Sa Kaew subdistrict, Tha Sala district, Nakhon Si Thammarat province produced and sold fried Kluai Khai chips in two flavors -- salty and sweet. In order to commercialize the products, the community enterprise members and product development experts jointly carried out this research study to develop a new recipe of fried Kluai Khai crisps and a process to upscale its production. The research process includes: 1) developing a new recipe for fried Kluai Khai chips; 2) transferring technology; 3) designing labels and packaging; and 4) applying for product standard certification. The two newly-developed fried Kluai Khai crisp products are Tom Yum and Laab flavors. From 100 panelists, 90% accepted the Tom Yum flavor, and 88% accepted the Laab flavor. The overall acceptance score stood at a moderate level of likeness. After the transfer of technology, the community enterprise members are able to produce new quality products that meet the standard. In addition, the new packaging and Thai FDA certification have helped expand the market and commercialize the products. The activities from the study promoted and disseminated knowledge on processing standard agricultural products in the community and raised 30% extra income to the community enterprise. It also results in the income circulation among farmers who grow Kluai Khai as the supply for the community enterprise’s fried Kluai Khai crisp products.